System and relation: the epistemological legacies of the structuralism to social theory - Tonkonoff, Sergio Esteban (2022)
Introduction Structuralism is one of the main currents of thought of the 20th century. Its developments concern to the most diverse aspects of both the social sciences and philosophy. Objective The objective of this article is to carry out a reconstruction of the structuralist social theory, seeking to reveal the problematic value of which it still carries. Specifically, we will try to show the way in which a series of traditional epistemological antinomies, typical of the human sciences, are unsettled. In particular, the oppositions between individualism and holism, materialism and idealism, substantialism and relationalism will be discussed. Method and technique For this, our method will be to concentrate on describing the basic theoretical syntax that structuralist research articulates around the concepts of relation and system. Results At least two results were obtained 1) it has been possible to clarify the characteristic way in which structuralism addresses and understands identities and social systems, 2) it is pointed out that the affirmation of the relational nature of identities together with the totalizing nature of systems it is the distinctive aporia of structuralism. Conclusions It is concluded that structuralism is not a holistic approach as classic as is usually thought, and it is suggested that the revelation of this problematic tension between relation and system is one of its major legacies.